THE INFLUENCE OF MOTIVATION ON WORK PRODUCTIVITY OF EMPLOYEES IN THE SUB-DISTRICT RAYA OFFICE SIMALUNGUN DISTRICT - Panjaitan, Hadi; G. Maffett, Mark; Saragih, Jopinus; Mayanta Tarigan, Hendri; Setiawan, Ben (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Qthe aim of this research isto find out how much influence motivation has on employee work productivity at the Subdistrict Office of Raya District, Simalungun Regency. This research used quantitative research with 19 sub-district employees as respondents.Data analysis used is multiple simple regression method with the F test and t test as a hypothesis test. QThe sampling technique in this study uses a saturated sampling technique, also known as a census.PIn this study, data analysis techniques used a simple regression analysis method.HThe results of the study indicate that work motivation and productivity simultaneously have a positive and significant effect on the performance of employees of the Sub-District Head Office, Raya District, Simalungun Regency, amounting to 0.819.This study also found that the influence exerted by work motivation and work productivity is very large.